Jihād and Crusade: Byzantine positions towards the notions of "holy war" - STOURAITIS, Ioannis (Byzantina Symmeikta, 2011)
The current study aims to re-approach the issue of holy war in Byzantium by exploring Byzantine attitudes towards the ideology of the Crusade in the period 1096-1024. The starting-point of the study is the comparison of Byzantine reactions towards the ideology of jihād, which date in the period before the Crusades, with the Byzantine reactions towards the Crusade during the twelfth and the beginning of the thirteenth centuries. The main part of the paper focuses on the exploration of Byzantine attitudes towards the two main Latin ideas that made the Crusade a notion of holy war, the ideas of deus vult and remissio peccatorum.